El azar como espacio positivo de indeterminación en la asimilación tomista de la física de Aristóteles - Minecan, Ana María (2018)
“Chance as a Positive Space of Indetermination in the Thomistic Assimilation of Aristotle’s Physics”. This article analyzes Thomas Aquinas’s assimilation of the Aristotelian theory of chance. The analysis highlights Thomas Aquinas’s unequivocal acceptance of Aristotelian philosophy, as well as the issues regarding which he abandoned the Aristotelian position by offering a new interpretation related to the role of chance in the context of the created cosmos. All in all, the confluence of these two great systems of thought –Aristotelian thought and late Medieval Christianity– provided new ways to understand nature, by expanding the scope of physics from the absolutely determined to the anomalous and irregular.